Variant Clustering Analysis Amorphophallus muelleri Blume Found in East Java Based on Molecular Marking CslA Mannan Synthase Encoder with PCR-RFLP Technique - Novie Ary Priyanti; Arik Arubil; Laras Estri Arumningtyas; Rodiyati Azrianingsih (Natural B, Journal of Health and Environmental Sciences, 2013)
Amorphophallus muelleri Blume is a ubiquotus plant found all over Indonesia and has the potential to be food substitute due to its high glucose content. This research was conducted to investigate the porang’s clustering based on CslA gene glucose coding by using PCR-RFLP technique. Porangs used as the subjet of this study were obtained from 4 different locations in East Java, wich are : (1) Nganjuk, (2) Madiun, (3) Blitar and (4) Jember, analysed by morphological characteristic and molecular traits. Morphological analysis showed that porang derived based on their stalk pattern. BlitarI, JemberI, MadiunI variant have large prismatic stalk patterns, Jember1 and Nganjuk2 have a tight prismatic stalk pattern. Glucomannan content analysis showed that highest content is from Blitar2 5,469% and the lowest is Madiun2 0,2313%. The amplification of CslA gene sequence using primary AkCslA680F and AkCslA1288R showed that CslA gene sequence was amplified on 200 bp. The cutting by using HaeIII restrictive enzyme produced two monomorphic band on 1000 bp and 2000 bp, and 8 polymorphic band on 100 bp-400 bp. The result of this analysis showed that porang had high diversity. The analysis of among variants clustering based on their molecules data showed that grouping fell into 3 clusters, which were: cluster I (JemberI, BlitarI and MadiunI variants), cluster II (Jember2, Blitar2 and Nganjuk2 variants) and cluster III (Blitar2 variant). The shortest distance was found between JemberI and BlitarI variants, while the furthest was found in Blitar2 variants.